Resilient and Responsible Smart Cities - Rodrigues, Hugo.; Fukuda, Tomohiro; Elias Bibri, Simon (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers current research studies which explore new technologies in architecture and urban practices which ensure the efficient management of cities' infrastructures and provide new solutions to the complex complications that may result in the tackling of challenges of population density, traffic planning, and city planning at the neighborhood scale or rather the scale of buildings and everyday life. It offers a path towards city resilience and sustainable infrastructure with the aim of meeting the demands of mega-cities. The primary audience of this book will be academics and professionals from the fields of architecture, urban planning, civil engineering, computer sciences, and mathematics. The book will aid them in their contributions to the implementation of sustainable development goals.
Building a Smart City from the periphery to the center: Application of Technological solutions for intelligent integration of peripheral neighborhoods -- Accelerated community resettlement by the means of robotic 3d-printing from conflicted highway projects: A case study of Yaounde, Cameroon -- Design and Implementation of AMI System of Electric and Water Meter -- Low-cost sensor node for air quality monitoring: verification of NO2 measurements against a commercial system -- Exploring The Relationship of India's Residential and Commercial Infrastructure Through Land Value -- A Conceptual Framework to Manage Social Risks for Smart City Development Programs -- Intelligent Irrigation System for Future Smart City -- Cities in the Era of Autonomous Vehicles: A Comparison Be-tween Conventional Vehicles and Autonomous Vehicles -- The need for Soft Infrastructure in a delta megacity -- Energy-Efficient Automatic Light Control System For Modern Urban City -- Photo-voice as Means to Experience Water Space: Exploring Traditional Water Knowledge in Khulna, Bangladesh -- Assessing the Urban Form of Hill Settlements, New-Shimla, India Using 3D GIS Tools.
Keywords: Landscape architecture; Sustainability; Architecture; Technology-Sociological aspects; Information technology; Landscape Architecture; Sustainability; Architecture; Information and Communication Technologies (ICT).